A critical review on In2S3-based nanomaterial for emerging contaminants elimination through integrated adsorption-degradation technique: Effect of reaction parameters and co-existing species - Mishra, Soumya Ranjan; Gadore, Vishal; Ahmaruzzaman, Md (Journal of hazardous materials letters, 2023)
The possibility of combined adsorption-degradation processes in wastewater treatment using nanomaterials based on indium sulfide (In2S3) is examined in this review paper. Regarding the synergistic adsorption and degradation of pollutants, In2S3 performs exceptionally well, making it a suitable choice for wastewater remediation. Insights have been given to the pollutant removal mechanism through this integrated technique. The synergistic removal process is affected by several operational factors, including pH, catalyst dose, pollutant concentration, and contact duration. This analysis highlights the significance of optimizing these parameters for optimal contaminant removal efficiency. The influence of co-existing species, including cations, anions, and organic compounds, on the integrated elimination process is further highlighted by a discussion of their role. Future research directions are suggested, including a better comprehension of underlying processes, investigation of hybrid nanocomposites, and evaluation of long-term stability and recyclability to enhance the applicability of In2S3-based nanomaterials. This study aids in the creation of effective and long-lasting wastewater treatment methods by using the potential of In2S3-based nanomaterials. [Display omitted] •Advantages of the integrated method over pristine adsorption and degradation methods has been discussed.•Mechanisms of the methods have been summarized.•Performance of In2S3-based nanocomposites for removing emerging contaminants has been summarized.•Role of reaction parameters on performance has been explored.•Effect of co-existing species on the catalyst efficacy is discussed.